When do electoral institutions trigger electoral misconduct?. Issue 2 (17th February 2018) - Ruiz-Rufino, Rubén
ABSTRACT: Drawing on two complementary mechanisms, this article explores the question of whether electoral institutions and conditions of electoral competition create incentives to promote electoral misconduct in young or developing democracies. The first mechanism explains how majoritarian institutions like disproportional electoral systems are more likely to trigger electoral fraud than consensus electoral institutions like proportional representation. However, for this mechanism to be activated, the incumbent must feel effectively threatened by the opposition. To better understand the way this mechanism works, the electoral history of the country also needs to be taken into consideration. Democracies which have a historical record of running clean elections are less likely to experience fraud than countries with a history of electoral misconduct. I test these theoretical claims using a dataset that contains relevant information for 323 parliamentary elections in 59 new or developing democracies in the period between 1960 and 2006. The empirical analysis shows a strong and robust empirical support for the two mechanisms.